Hg(II) Ion-Selective Electrodes with PVC Membranes Based on Bis-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one - Isildak, Omer; Yildiz, Ilyas; Erenler, Ramazan; Dag, Besir; Isildak, Ibrahim (OXFORD UNIV PRESS, 2022)
A new solid-state contact potentiometric membrane electrode was developed based on bis-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one (ionophore), which acts selectively towards the mercury(II) ion. The ionophore was synthesized by the treatment of an amino derivative with oxybis dibenz-aldehyde. The potentiometric behavior of an electrode was investigated in the concentration range from 1.0 x 10(-2) to 1.0 x 10(-6) mol L-1 for mercury(II) ion. The electrode displayed a good linearity (R-2 = 0.9997) with the detection limit of 1.2 x 10(-7) mol L-1 and showed a very high selectivity against Hg(II) ion without being affected by the presence of interfering ions. The electrode exhibited a potential change of 62.0 +/- 2.0mV for each ten-fold increase in concentration of mercury(II) ion. Potentiometric response of the electrode was investigated in the pH range from 3.0 to 10.0. In addition to this electrode being used to determine mercury(II) in different water samples, it can also be used with EDTA as an indicator electrode in the potentiometric titration of mercury(II) ion. Since the developed electrode displayed good potentiometric performance, it has potential to be used in environmental and biological samples for detection of mercury(II) ions.
Keywords: Mercury(II); Pyrazol derivated; Selective electrode; SENSOR; MERCURY; ENONES; WATER; Chemistry